Supplying wine, olive oil and fish products to the Lower Danube frontier (2nd-7th century AD): The case of Dinogetia - Opaiț, Andrei; Barnea, Alexandru; Barnea, Iuliana; Grigoraș, Bianca; Potra, Ioana (Rei Cretariae Romanae Fautorum Acta, 2022)
The authors present amphora discoveries made at Dinogetia during the last eighty years of excavations. The large quantities of ceramic material serve as a proxy for the wine, olive oil, and fish-based commodities imported to this remote fortress. It sheds new light on ancient supply modalities, which included both free trade and state-controlled provisions for the Roman troops stationed at Dinogetia. At the same time the results of this study can be extrapolated to many other small fortresses on the lower Danube and have good parallels at Iatrus, Capidava, and Murighiol. If for the large variety of vintage wine and fish-based products we can infer a private trade, for olive oil, especially in the later Roman period, we may infer the activities of the annona militaris. The presence of these imports until the very end of this fortification shows that the imperial authorities paid good care to the limitanei, which were not simply paysan-soldiers but active and efficient defenders of the Roman frontier.